Elastic scattering of electrons from Rb, Cs and Fr atoms - Gangwar, Reetesh Kumar; Tripathi, A. N.; Sharma, Lalita; Srivastava, Rajesh (Journal of physics. B, Atomic, molecular and optical physics, 2010)
Differential, integrated elastic, momentum-transfer and total cross sections as well as differential S, T and U spin parameters for scattering of electrons from rubidium, caesium and francium atoms in the incident energy range up to 300 eV are calculated using a relativistic Dirac equation. The projectile electron-target atom interaction is represented by both real and complex parameter-free optical potentials for obtaining the solution of a Dirac equation for scattered electrons. The Dirac-Fock wavefunctions have been used to represent the Rb, Cs and Fr target atoms. The results of differential cross sections and spin asymmetry parameter S for e-Rb and e-Cs have been compared with the available experimental and theoretical results. Detailed results are reported for the elastic scattering of electrons from the ground states of a francium atom for the first time in the wide range of incident electron energies. The results of electron-Fr elastic scattering show the similar features to those obtained in the case of e-Rb and e-Cs elastic scattering.